3(u+6)=7u

Simple and best practice solution for 3(u+6)=7u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(u+6)=7u equation:


Simplifying
3(u + 6) = 7u

Reorder the terms:
3(6 + u) = 7u
(6 * 3 + u * 3) = 7u
(18 + 3u) = 7u

Solving
18 + 3u = 7u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-7u' to each side of the equation.
18 + 3u + -7u = 7u + -7u

Combine like terms: 3u + -7u = -4u
18 + -4u = 7u + -7u

Combine like terms: 7u + -7u = 0
18 + -4u = 0

Add '-18' to each side of the equation.
18 + -18 + -4u = 0 + -18

Combine like terms: 18 + -18 = 0
0 + -4u = 0 + -18
-4u = 0 + -18

Combine like terms: 0 + -18 = -18
-4u = -18

Divide each side by '-4'.
u = 4.5

Simplifying
u = 4.5

See similar equations:

| 9y-8y=12 | | x-4-1=7 | | 2x^2+13x-30=0 | | 4(13n+4)=-36 | | 3u+30=-3(u+6) | | 5.6-2a+1.4=54 | | (8j-3l+9)6= | | 2(6-y)-7y=-7 | | (6+w)(5w+3)=0 | | 4t+5=3t+5+t | | z^2+13z=-42 | | 33x=3x^2-7x-18 | | .7(v+3.2)=-.28 | | -14x^2+54x-36=0 | | 3-x(x-5)=5 | | 24k^2-31k-36=k | | 0.6(x-1.3)=.15 | | 27-4t-12t=t-7 | | X^2-5x-29=0 | | 12x+3x=100+22 | | 64=((2*h)*h)/2 | | 5x+5x=70 | | x^2-6-5x=0 | | -8m-3m=16 | | 64=(2h*h)/2 | | 7(4n-5m)= | | (8i)(4i)(9i)= | | 13x^2+44x+14=7x^2 | | (X-5y)(x+3y)= | | y=x^3-81x | | 3x^2-15-2x=0 | | 72=3(3z) |

Equations solver categories